Analisis Hambatan Guru dalam Penerapan Model Problem Based Learning pada Pembelajaran IPS Kelas IV di SDN 090 Cibiru Bandung - Fitria Nur Auliah; Natasya Febriyanti; Tin Rustini (Journal on Education, 2023)
This research is motivated by the fact that there are still teachers who have difficulty in applying the learning model well in classroom learning, so the researchers intend to examine what are the obstacles or obstacles in the application of the PBL learning model in social studies learning in elementary grade IV. Teachers as one of the important components in the learning process need to pay attention to the needs and characteristics of their students in preparing quality learning. To achieve this, teachers must be creative in choosing the right learning model and also pay attention to the characteristics of elementary school students. One of the models commonly used by teachers in social studies learning is the problem based learning (PBL) model. The PBL learning model is a learning model that makes problems as the basis for student learning. Based on the research that the researcher has done through descriptive qualitative research methods with the research subject of class IV teachers at SDN 090 Cibiru, it was found that various obstacles became obstacles for teachers in implementing the PBL learning model to the fullest. These obstacles are: (1) inadequate facilities; (2) teacher readiness; (3) limited time; and (4) barriers from within the classroom and students. The data collection techniques were carried out by interview, observation, and documentation techniques.